Hypertension is the underlying cause of death assessed at the autopsy of individuals - Juliana Chaves Coelho; Renata Eloah de Lucena Ferretti-Rebustini; Claudia Kimie Suemoto; Renata Elaine Paraizo Leite; Wilson Jacob-Filho; Angela Maria Geraldo Pierin
ABSTRACT Objective: To analyze hypertension and its relationship with the causes of death identified by the autopsy. Method: Cross-sectional study analyzed 356 participants belonging to the Brazilian Aging Brain Study Group, over 50 years of age, autopsied at the Sao Paulo Autopsy Service between 2004 to 2014. A clinical interview was conducted with the informant of the deceased. Hypertension was defined by reporting the disease and/or use of antihypertensive medication, by the informant of the deceased. Descriptive analyzes and bivariate and multivariable associations were performed. Results: The prevalence of hypertension was 66.2% and it was the second leading cause of death (25.6%) identified by autopsy, preceded by atherosclerosis (37.8%). The variables associated with hypertension were: female gender (OR=2.30 (1.34-3.90)); living with partner [OR=0.55 (0.32-0.92)]; Body Mass Index [OR=1.14 (1.08-1.22)] and history of diabetes [OR=2.39 (1.34-4.27)]. Conclusion: The prevalence of hypertension was high, and it was the second most common underlying cause of death. The gold standard for the definition of cause of death, the autopsy, shows important results, which confirmed the relevance of hypertension as a public health problem.